ANALISIS MIKROBIOLOGI JAJANAN MINUMAN DI SEKITAR SEKOLAH DASAR PADA WILAYAH JEMURWONOSARI, SURABAYA - Endah Prayekti (Jurnal SainHealth, 2017)
Snack as food and beverages, present vastly in Surabaya. Start from street vendor to famous stores. The distribution of these snacks trader often found in schools, from primary to high school. Common problems from these food dan baverages sales is their hygine. With a low sales price, other raised problem are the using of raws material for snack production which lead to hazard microbial contamination. This reaserch aim is to monitors the quality of beverages on microbiology that been sold in around primary school of Jemur Wonosari District, Surabaya. Two microbiology parameters that been analize were coliform bacterial and Escherichia coli number. Beverages sample that been used were 9 samples, then analize using most propable number using 15 tube series. The Results then analize descriptively. From 9 samples, all were exceed the standar quality according to Kepmenkes RI No.492/MENKES/PER/2010.